Contamination of dietary supplements and positive drug tests in sport - Maughan, R. J. (Journal of Sports Sciences, 2005)
The use of dietary supplements is widespread in sport and most athletes competing at the highest level of competition use some form of dietary supplementation. Many of these supplements confer no performance or health benefit, and some may actually be detrimental to both performance and health when taken in high doses for prolonged periods. Some supplements contain excessive doses of potentially toxic ingredients, while others do not contain significant amounts of the ingredients listed on the label. There is also now evidence that some of the apparently legitimate dietary supplements on sale contain ingredients that are not declared on the label but that are prohibited by the doping regulations of the International Olympic Committee and of the World Anti-Doping Agency. Contaminants that have been identified include a variety of anabolic androgenic steroids (including testosterone and nandrolone as well as the pro-hormones of these compounds), ephedrine and caffeine. This contamination may in most cases be the result of poor manufacturing practice, but there is some evidence of deliberate adulteration of products. The principle of strict liability that applies in sport means that innocent ingestion of prohibited substances is not an acceptable excuse, and athletes testing positive are liable to penalties. Although it is undoubtedly the case that some athletes are guilty of deliberate cheating, some positive tests are likely to be the result of inadvertent ingestion of prohibited substances present in otherwise innocuous dietary supplements.